Implementing the Chaotic Permutation Multicircular Cryptography Technique using Asymmetric Key - Aria Lesmana; Ruki Harwahyu; Yohan Suryanto (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
In digital computing, cryptographic methods considers performance in both speed and security. This study aims to explore and improve a permutation-based symmetric chaotic cryptography technique called Chaotic Permutation Multicircular (CPMC). In this study, a method is proposed to implement asymmetric key system from CPMC technique by generating a reverser key for reverting the permutation result of CPMC encryption back to its original arrangement using the same function as encryption. The reverser key alongside the CPMC key act as encryption and decryption key pair. The pair key generation and cryptographic function utilizes the encryption function of CPMC technique dubbed CPMC Shrinking algorithm. Asymmetric implementation can simplify CPMC technique by also using CPMC Shrinking algorithm for decryption, therefore enabling it as a single function for encryption and decryption. The asymmetric single function cryptography test show improvement in speed from faster cryptographic speed in decryption compared to initial implementation by average of 75.87%